👤

1. Descompuneti:
a) (3x - 1)²-9;
c)(x2 - 4x + 4) - 9y²;
e) (2x + 5)(3x - 1) - 4(2x + 5);
b) 49x² - 100;
d) (1 + 4x + 4x²) - 25;
f) (3x - 2)(x + 7) + (3x-2)(x-5)
va rog ajutati-maaaa❤❤​


Răspuns :

°a. (3x - 1)^2 - 9 = (3x -1 - 3 ) × ( 3x - 1 + 3 ) = (3x -4 )×(3x + 2 ) ;

°b. 49x^2 - 100 = 7^2 x^2 - 10 ^2 = ( 7x)^2 - 10^2 = (7x - 10 )×(7x + 10 ) ;

°c. ( x2 - 4x + 4) - 9y^2 = ( 2x -4x + 4 ) - 9y^2 = ( -2x + 4 ) - 9y^2 = -2x + 4 -9y^2 ;

°d. (1 + 4x +4x ^2 ) - 25 = ( 1 + 2x)^2 - 25 = (1+ 2x -5) × (1+ 2x + 5 ) = (-4 + 2x )×(6+2x) = (-2 ( 2-x)) × 2 (3 + x ) = -2 × 2(2-x) × (3 + x) = -4 (2-x) × (3+x) ;

°f. (3x - 2 )( x + 7) + (3x - 2 )(x-5) = (3x - 2 ) × ( x + 7 + x - 5 ) = ( 3x - 2 )×(2x+2) = (3x-2) ×2 (x + 1 ) = 2(3x -2) × (x + 1) ;